The power of two a twin triumph over cystic fibrosis - Stenzel Byrnes, Isabel, 1972- (University of Missouri Press, 2007)
"Born in 1972, twins who share this life-threatening disease give an honest portrayal of their struggle to live normal lives, their interdependence, day-to-day health care, the impact of chronic illness on marriage and family, and the importance of a support network to continuing survival"--Provided by publisher.